Information sourcing in an automated academic library (2010)
Purpose - Information seeking is a fundamental human process closely related to learning and problem solving, thus the information sourcing characteristics of users of the Kenneth Dike Library, University of lbadan is examined with a view to evaluating their use of modern Information and Communication Technology (ICT) facilities provided. Use patterns, user satisfaction with (he ICT facilities, and user preference of manual and electronic facilities provided are evaluated Methodology. Descriptive survey research to appraise the adequacy of modern ICT in the library was carried out. Questionnaire, interview and participatory observation methods were used Findings - The results show that majority of the users (81%) prefer the new ICT facilities to the manual, even though they encounter difficulties in use. Lack of constant power supply, limited access to online resources, lack of adequate user and staff training and non-creation of awareness for the ICT facilities is identified as some of the problems. The CD-ROM and the Internet are the most frequently consulted ICT facilities, while many called for enhancement and updating of the book/journal collection. Originality/value - The research brings to the fore types of ICT needed and sourced for by users, and the need for information providers and users to adapt to the changes. Challenges facing the library in information provision (IS well as the prospects are discussed, and recommendations made for future improvement and continuous evaluation.